2015
DOI: 10.9734/jsrr/2015/17128
|View full text |Cite
|
Sign up to set email alerts
|

Community Based Study of Cerebrovascular Risk Factors in Tripoli-Libya (North Africa)

Abstract: A stroke is the leading cause of adult mortality and disability. It is the second most common cause of death globally and may soon become the first cause of death worldwide. Among the most important risk factors for stroke are advanced age, hypertension, diabetes, previous stroke or transient ischemic attack. Hypertension and diabetes are the most important and frequent modifiable risk factors of stroke. Objectives: Estimate the most important risk factors associated with stroke in African population by using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 20 publications
(21 reference statements)
1
4
0
Order By: Relevance
“…Mortel et al [20] reported that diabetes is second to hypertension as a risk factor for stroke, followed by heart disease and smoking which also showed by this study results and by Shambesh et al [14], were DM and hypertension are heading risk factor Followed by CHF.…”
Section: Fig 3 Showing Csrc Score Levels Among Dm Patientssupporting
confidence: 78%
See 4 more Smart Citations
“…Mortel et al [20] reported that diabetes is second to hypertension as a risk factor for stroke, followed by heart disease and smoking which also showed by this study results and by Shambesh et al [14], were DM and hypertension are heading risk factor Followed by CHF.…”
Section: Fig 3 Showing Csrc Score Levels Among Dm Patientssupporting
confidence: 78%
“…The prevalence of DM among our participants (7497 individuals) in study done by Shambesh et al [14] was 39% (2908 patients), among males and females was 54.1% and 45.9% respectively (P =0.0001). Among different age groups, males have higher rates compared to females except in very young (10)(11)(12)(13)(14)(15)(16)(17)(18)(19) and very old (>80) as shown in Table 3 and Fig. 1.…”
Section: Diabetes Mellitus (Dm) Prevalencementioning
confidence: 50%
See 3 more Smart Citations